PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS LECTORA INSPIRE PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR UNTUK KELAS X SMA/MA - Nurul Hasanah; R. Usman Rery; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this research is to develop of based Lectora Inspire learning media on atomic structure and periodic system of the element for ten class of senior high school / islamic senior high school. The objects of this research is Lectora Inspire learning media designed in accordance with the KTSP curriculum competences. Lectora Inspire learning media consist of teaching materials and test materials in the form of sample questions and exercises which are equipped with feedback and evaluation with scoring Method of this research which is used by the researcher is Research and Development (RnD) with its development process using a model of ADDIE (Analysis, Design, Development, Implementation dan Evaluation). ADDIE model development research is conducted only up to the development phase, for the purpose of this research was limited to develop and produce a valid learning media to be implemented based on an assessment of validator. The research has been conducted for 5 months including lesson and learning media analysis phase, the design phase, the development phase which consists of product development and product validation. The instruments of this research are validity questioners for lesson and media expert which includes the designing aspect, pedagogical aspects, aspects of content and aspects of the ease of use that was given to 10 validators that is 3 lesson expert and 7 media expert matter experts. At the development phase is condusted 2 times validity phase. The result of this research shows that validity obtained percentage scoring average of 87.20% with a valid category. Based on the result and discussion can be concluded that Lectora Inspire learning media which are developed on atomic structure and periodic system are valid for use in chemistry learning for ten class of senior high school / islamic senior high school.Keywords : Computer Based Learning, Lectora Inspire, Atomic Structure and Periodic System of The Element